Research Guideline Recommendations for Research on Stem Cells, Human Embryos, and Gene Editing - Susanna R. Var; Phoebe Strell; Anala Shetty; Alex Roman; Isaac H. Clark; Andrew T. Crane; Gary L. Dunbar; Kyle Fink; Andrew W. Grande; Ann M. Parr; Julien Rossignol; Paul R. Sanberg; et al. (Cell Transplantation)
Recent advances in biomedical technologies have extended the boundaries of previously established regulatory guidelines pertaining to stem cell research. These guidelines constrained the study of human pluripotent stem cells (hPSCs) and their derivatives from use under various conditions, including the introduction of hPSCs into the brains of host animals because of concerns of humanizing the brains of animal species. Other guidelines constrained the use of hPSCs in creating human-animal chimeras because of the potential contribution of human stem cells not only to the brain but also to the germline. Some regulatory guidelines forbid the growing of human embryos ex vivo beyond the stage of primitive streak development because of concerns regarding the creation of human forms of life ex vivo . At the subcellular level, there are guidelines regulating the transfer of mitochondria within human embryos. At the molecular level, there are guidelines regulating genome editing to prevent permanent genetic alterations in germline cells. These and other issues related to stem cells have been reviewed, and new research guidelines established by the International Society for Stem Cell Research (ISSCR) for its membership. Because many of the recommended changes by the ISSCR impact research being conducted by members of the American Society for Neural Therapy and Repair (ASNTR), the ASNTR established a task force to review relevant recommendations by the ISSCR to determine which new guidelines to adopt for research conducted by the ASNTR society membership. The final ASNTR recommendations are presented in this document.